2014
DOI: 10.1371/journal.pone.0111021
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying mRNA and MicroRNA with qPCR in Cervical Carcinogenesis: A Validation of Reference Genes to Ensure Accurate Data

Abstract: A number of recent studies have catalogued global gene expression patterns in a panel of normal, tumoral cervical tissues so that potential biomarkers can be identified. The qPCR has been one of the most widely used technologies for detecting these potential biomarkers. However, few studies have investigated a correct strategy for the normalization of data in qPCR assays for cervical tissues. The aim of this study was to validate reference genes in cervical tissues to ensure accurate quantification of mRNA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…A major limitation of our study was the lack of real-time quantitative PCR-based validation of our identified miRs. However, unlike the known-reference miRs in cervical cancer and colorectal cancer [41,42], the reference miRs in DN remain unknown. An alternative approach to overcome this problem we would like to suggest is to test our reported deregulated miRs in various clinical and experimental models.…”
Section: Discussionmentioning
confidence: 99%
“…A major limitation of our study was the lack of real-time quantitative PCR-based validation of our identified miRs. However, unlike the known-reference miRs in cervical cancer and colorectal cancer [41,42], the reference miRs in DN remain unknown. An alternative approach to overcome this problem we would like to suggest is to test our reported deregulated miRs in various clinical and experimental models.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was purified in a subsequent stage by means of the miRNA Absolutely RNA Kit (Agilent Technologies). The RNA quality was assessed by a NanoDrop 2000 Spectrophotometer (ThermoScientific, Wilmington, DE, USA) and 1% agarose gel electrophoresis (Bustin et al, 2009;Leitão et al, 2014;Rueda-Martínez et al, 2014). After this, 1 μg of RNA samples of a suitable quality (an OD260/280 from 1.8 to 2.1 and intact rRNA subunits -28S and 18S) was used to generate the cDNA with the aid of a miScript II RT kit (Qiagen).…”
Section: Total Rna Extraction and Cdna Synthesismentioning
confidence: 99%
“…Reference genes that had been previously validated by the group of cervical tissues, were used to obtain mRNA expression levels (26???). In this way, the geometric mean of GAPDH and the ACTB reference genes, was used to calculate the relative expression of IL-1β and IL-18 mRNAs (Leitão et al, 2014). Every qPCR reaction was run in duplicate for each sample to minimize pipetting error (Nolan et al, 2006).…”
Section: Real-time Quantitative Polymerase Chain Reaction (Qpcr)mentioning
confidence: 99%
“…At the mRNA level, STING expression was analyzed in ficoll-isolated PBMC using semi-qPCR (RPLP0 and PGK1 genes were used as endogenous controls [26]): similar to flow cytometry results, in PBMC from patients with preinvasive/microinvasive cancer (stage 0-IA), STING-mRNA Figure 7A) suggesting the need for T cell (CD4/CD8) separation in further analysis. STING-mRNA expression was also assessed in samples of HPV-negative morphologically normal epithelium (control), HPV-positive precancerous lesions of the cervix, carcinoma in situ and microinvasive carcinoma (relative to four genes-EEF1A1, ACTB, GAPDH, and RPLP0-taken as endogenous controls due to their proved constitutive expression in cervical tissues [27]) ( Figure 7B). In contrast to lymphocytes, a considerable (up to 50%) proportion of pathological samples in each patient group showed elevated STING expression as compared with normal noninfected epithelium (though the group mean values did not differ statistically).…”
Section: Sting Mrna Expression In Peripheral Blood Mononuclear Cells mentioning
confidence: 99%